INFLUENCE OF SACCOS IN ENTREPRENEURIAL CAPACITY DEVELOPMENT IN DAGORETTI SOUTH CONSTITUENCY, KENYA - Njoroge, Sammy Mwatha; Kagiri, Dr. Assumpta (Journal of Entrepreneurship and Project Management, 2017)
Purpose: The main objective of this study is to find out the influence of SACCOs in entrepreneurial capacity development in Dagoretti South constituency, Nairobi, Kenya. To successfully achieve the study objective the research was guided by the following specific objectives: - To establish the extent to which disbursed credit by SACCOs help in entrepreneurial capacity development in Dagoretti South constituency; To determine the extent to which deposits/share capital help in entrepreneurial capacity development in Dagoretti South constituency; To find out how SACCOs investment portfolios help in entrepreneurial capacity development in Dagoretti South constituency. To find out how information dissemination helps in entrepreneurial capacity development in Dagoretti South constituency Methodology: The study employed a descriptive survey research design to find out the role of SACCOs in entrepreneurial development in Dagoretti constituency. The study adopted a census study. A questionnaire was used as primary data collection instruments. The collected data was examined and checked for completeness and comprehensibility. The data was then summarized, coded and tabulated with the help of the Statistical Package for Social Sciences (SPSS 17.0) Data presentation was done by the use of pie charts, bar charts and graphs, percentages and frequency tables. Results: With all the independent variables having p < 0.05, this indicates that there is a significant relationship among all the four variables with the influence of SACCOs in entrepreneurial capacity development in Dagoreti South constituency. From the results, a unit % increase in Access to Loans would result to 44% decrease in share capital. Additionally, a unit % increase in entrepreneurship education would result to 36% increase on the influence of SACCOs in entrepreneurial capacity development in Dagoretti South constituency. Having the composite mean as 3.68053 and the standard deviation as 0.4768, meant that the respondents agreed that Access to Loans, Share capital, and Entrepreneurship education had a significant influence on SACCOs in influencing entrepreneurial capacity development in Dagoretti South constituency. Recommendation: With the Kenya government steering towards industrialization in her vision 2030, entrepreneurship training should be the first gear towards this direction. Many countries have prospered as a result of constructing and embracing entrepreneurial culture among their population. SACCOs are a good starting point especially in rural-urban areas where government devolution tentacles have started to spread. SACCOs should strive to maximize on the earnings to build the institutional capital. This institutional capital ensures the permanence and growth of the SACCOs even in turbulent economic times. In fact, it would help the SACCOs to grow and, remain economically and financially viable. Such growth should be enhanced by effective financial practices not to mention entrepreneurial training.